2017
DOI: 10.1002/jcla.22113
|View full text |Cite
|
Sign up to set email alerts
|

Fecal calprotectin level in healthy children aged less than 4 years in South Korea

Abstract: Background Fecal calprotectin (FC) is non‐invasive inflammatory marker indicating various bowel diseases. However, the median‐specific cut‐off values and the standard deviations (SD) of the FC levels in each age group <4 years were not elucidated. Methods Healthy volunteers were enrolled from four kindergartens. A questionnaire was used to confirm that the children met the inclusion criteria, and several demographics and history of bowel symptoms were collected. The FC level was measured. Results A total of 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
2
12
0
1
Order By: Relevance
“…Calprotectin is secreted extracellularly from stimulated neutrophils and the FC levels of healthy children exhibit a downward trend with increasing age and reach the adult level by the age of four 19,20. This finding is consistent with recent FC study in healthy children aged less than 4 years in South Korea 21. The children were divided into six age groups and the median FC values was 135 μg/g in 7–12 months group, 65 μg/g in 13–18 months group, 55 μg/g in 19–24 months group, 40 μg/g in 25–30 months group, 21 μg/g in 31–36 months group, and 12 μg/g in 37–48 months group.…”
Section: Discussionsupporting
confidence: 91%
“…Calprotectin is secreted extracellularly from stimulated neutrophils and the FC levels of healthy children exhibit a downward trend with increasing age and reach the adult level by the age of four 19,20. This finding is consistent with recent FC study in healthy children aged less than 4 years in South Korea 21. The children were divided into six age groups and the median FC values was 135 μg/g in 7–12 months group, 65 μg/g in 13–18 months group, 55 μg/g in 19–24 months group, 40 μg/g in 25–30 months group, 21 μg/g in 31–36 months group, and 12 μg/g in 37–48 months group.…”
Section: Discussionsupporting
confidence: 91%
“…On contrary, fecal calprotectin was higher during the first year of life as we observed here and as has been reported [6,7,[17][18][19]. It has been suggested that the increased permeability of the gut might increase the influx of inflammatory cells in the gut in babies and thus, have an impact on the higher fecal calprotectin values.…”
Section: Discussionsupporting
confidence: 83%
“…For adults and children, <50 μg/g of FC in stool has been considered within normal limits ( 9 ). However, FC concentration has age-dependent variation in children, especially those younger than 4 years, and increases in infants ( 10 , 11 ). Normally, a high level of FC was reported in healthy neonates, and the usefulness of this marker remains controversial in the neonatal period ( 2 ).…”
Section: Introductionmentioning
confidence: 99%